Prevalence of hypothyroidism in different occupational groups of Bangladeshi population - MA Sayeed (IMC Journal of Medical Science, 2019)
Background and aims: Hypothyroidism is a common global endocrine disorder. The magnitude of hypothyroidism at community level in Bangladesh is unknown except some clinic-based studies. The present study was undertaken to determine the prevalence of hypothyroidism in different occupational groups of Bangladeshi population and to assess the risks related to it.